2003
DOI: 10.1182/blood-2002-05-1549
|View full text |Cite
|
Sign up to set email alerts
|

Levels of phospho-Smad2/3 are sensors of the interplay between effects of TGF-β and retinoic acid on monocytic and granulocytic differentiation of HL-60 cells

Abstract: We have investigated the role of Smad family proteins, known to be important cytoplasmic mediators of signals from the transforming growth factor–β (TGF-β) receptor serine/threonine kinases, in TGF-β–dependent differentiation of hematopoietic cells, using as a model the human promyelocytic leukemia cell line, HL-60. TGF-β–dependent differentiation of these cells to monocytes, but not retinoic acid–dependent differentiation to granulocytes, was accompanied by rapid phosphorylation and nuclear translocation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 49 publications
3
55
1
Order By: Relevance
“…4B) and expression (Fig. 4C) of target genes during granulocytic maturation of HL-60 cells, induced to differentiate by treatment with ATRA (34)(35)(36) over the course of 4 days. Note that Gfi-1 is also expressed in HL-60 cells (Fig.…”
Section: Gfi-1 Recruitment During Granulocytic Differentiation Of Hl-mentioning
confidence: 99%
“…4B) and expression (Fig. 4C) of target genes during granulocytic maturation of HL-60 cells, induced to differentiate by treatment with ATRA (34)(35)(36) over the course of 4 days. Note that Gfi-1 is also expressed in HL-60 cells (Fig.…”
Section: Gfi-1 Recruitment During Granulocytic Differentiation Of Hl-mentioning
confidence: 99%
“…Similarly, T-RA increases expression of TGFb1 and the TGFb receptor in HL60 cells leading to an autocrine antiproliferative growth loop (Falk et al, 1991;Nunes et al, 1996). However, it has been shown that T-RA reduces SMAD phosphorylation in HL60 cells, thus negatively regulating TGFb-signalling and differentiation into monocytes (Cao et al, 2003). T-RA has also been shown to regulate TGFb expression and proliferation in embryonic palate mesenchymal cells (Nugent et al, 1998) and more recently, to regulate TGFb in the embryonal yolk sac to ensure visceral endoderm survival (Bohnsack et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…263,264 The differential effect of TGFb on monocytic versus granulocytic differentiation may be explained by the enhancement of Smad2/3 phosphorylation and nuclear translocation during vitamin D3-induced monocytic differentiation, and the reduction of Smad2/3 phosphorylation and nuclear accumulation during ATRA-induced granulocytic differentiation. [265][266][267] Conclusions/future perspectives Emerging evidence indicates that multiple signaling pathways are activated during cytokine-induced myeloid differentiation and that these pathways may play critical roles in facilitating the differentiation process. Moreover, the impact that activation of a given pathway has on normal myeloid differentiation may be markedly different from the impact that is seen when that pathway is activated in a differentiation-defective leukemia.…”
Section: Pi3k-akt Pathwaymentioning
confidence: 99%